2019
DOI: 10.1016/j.renene.2019.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Design, modelling, energy and exergy analysis of a parabolic cooker

Abstract: A functional parabolic solar cooker was designed and constructed to serve as an alternate renewable source of energy for cooking and to also reduce the adverse effects of other sources of energy on the environment. The solar cooker was fabricated using cheap, locally sourced available materials in Nigeria. Experimental investigation was carried out on the produced model in Omu-Aran Metropolis, Kwara State, Nigeria in December 2016. Thereafter other investigations were carried out from January to December 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…[27] Receiver coating material Silicon based system preferable [28] Parabolic dish solar cooker with aluminium black coated receiver Efficiency of 7% was realized [29] Insulated wooden box receiver with glass cover and black painted pot placed inside Efficiency of 39% was registered [30] Material for cooking vessel (aluminium and galvanized iron) for parabolic solar dish Aluminium achieved higher temperature and Less cooking time [31] Comparison of two modes of the system (cooker and water heater)…”
Section: Referencesmentioning
confidence: 99%
“…[27] Receiver coating material Silicon based system preferable [28] Parabolic dish solar cooker with aluminium black coated receiver Efficiency of 7% was realized [29] Insulated wooden box receiver with glass cover and black painted pot placed inside Efficiency of 39% was registered [30] Material for cooking vessel (aluminium and galvanized iron) for parabolic solar dish Aluminium achieved higher temperature and Less cooking time [31] Comparison of two modes of the system (cooker and water heater)…”
Section: Referencesmentioning
confidence: 99%
“…Moreover, the study revealed that there was a scope for further improvement in the heat loss coefficient of the system by using better insulation, shape and structure of the receiver. Onokwai et al (2019) designed and fabricated a solar box-parabolic dish cooker by using locally available materials in Nigeria on which modelling, and analysis of exergy and energy efficiencies were done. The receiver, which was not an integral part of the dish, was made of an insulated wooden box with a glass cover and a cooking pot, painted black placed inside.…”
Section: Previous Studies On Technical Performance Of Solar Cooking S...mentioning
confidence: 99%
“…Solar reflecting systems for research activities, e.g. plane mirrors, need high quality and good specular reflectance properties [19][20][21][22][23][24][25]. Plane mirror of 2 mm thickness was used putting into consideration the cross weight of the parabolic dish.…”
Section: Materials Selectionmentioning
confidence: 99%